2017
DOI: 10.1002/micr.30247
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic mapping of the upper limb with lymphedema before lymphatic supermicrosurgery by mirroring of the healthy limb

Abstract: This technique allowed to preoperatively map UL lymphatics even if diffuse DB was present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 23 publications
0
38
0
Order By: Relevance
“…In both studies, all subscales and the overall quality of life improved significantly (p < 0.01). Gentileschi et al reported a significant increase in the average overall score using the LYMQOL at 6 months after LVB for treatment of upper extremity lymphedema in 16 patients (p < 0.001) [38]. Salgarello et al used the LYMQOL to evaluate outcomes of LVB for treatments of either upper extremity (n = 44) or lower extremity (n = 26) lymphedema at an average of 8.5 months [39].…”
Section: Lymqolmentioning
confidence: 99%
“…In both studies, all subscales and the overall quality of life improved significantly (p < 0.01). Gentileschi et al reported a significant increase in the average overall score using the LYMQOL at 6 months after LVB for treatment of upper extremity lymphedema in 16 patients (p < 0.001) [38]. Salgarello et al used the LYMQOL to evaluate outcomes of LVB for treatments of either upper extremity (n = 44) or lower extremity (n = 26) lymphedema at an average of 8.5 months [39].…”
Section: Lymqolmentioning
confidence: 99%
“…The other studies did use validated tools to asses QoL. However, these are studies with small sample sizes (range 10–74 patients) and relatively short follow-up (range 6–12 months) [ 10 , 22 , 23 , 33 35 ]. To the best of our knowledge, the current study may cover the largest population with the longest follow-up, assessing QoL improvement over different periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…20,2729 However, preoperative detection of lymphatic vessels using ICG lymphography was difficult in most of late-stage UEL patients, because linear patterns were usually concealed by stardust patterns or diffuse patterns in progressive lymphedema. 2224,26,2932 Furthermore, ICG lymphography has limitations in detecting lymphatic vessels real-timely, because strong light of an operating microscope and stardust patterns around the incision sites usually influences delicate ICG fluorescent imaging. In this study, real-time ICG videolymphography under operating microscope light could detect 20 lymphatic vessels for LVAs from 24 stardust or diffuse pattern incision sites intraoperatively (83.3% detection rate).…”
Section: Discussionmentioning
confidence: 99%
“…Lymphatic vessels at the arm in UEL patients are relatively small in diameter than that of lower extremity lymphedema patients. 914,20,26,32 When lymphatic vessels are under 0.30 mm in diameter, it is not easy to detect lymphatic vessels from connective tissue fibers or nerves in lymphedematous fibrotic subcutaneous tissues even for experts. With our real-time ICG videolymphography, lymphatic vessels were easily detected from these structures.…”
Section: Discussionmentioning
confidence: 99%